Analysis of Waste Management at TPS Perumnas Mandala, Kec. Percut Sei Tuan - Nasution, Dinda Azria; Nanda, Meutia; Azzahra, Fatimah; Rizqika, Indah; Hazrin, Yosita (PROMOTOR, 2024)
Indonesia is a country with a very large population and the trend continues to increase. The North Sumatra region produces the 7th largest volume of waste in Indonesia, with around 882,033 thousand tons of waste generated. Perumnas Mandala is one of the areas in the city of Medan that has a dense population, where the temporary disposal site (TPS) is not far from residential areas. So the problem of waste management arose at the Perumnas Mandala waste landfill, Percut Sei Tuan district. The aim of this research is to determine waste management at TPS Perumnas Mandala Kec.Sei Tuan. This research uses a qualitative approach with descriptive research type. The population in this study were all residents around Perumnas Mandala. The samples in this study were informants, namely the head of waste officers at the Perumnas Mandala TPS, 2 waste officers at the Perumnas Mandala TPS, and several residents around the Perumnas Mandala TPS, namely around 5 communities around the Perumnas Mandala TPS, using a purposive sampling technique. The research results show that waste management at TPS is still not good due to several factors such as lack of waste transportation facilities, lack of waste officers in managing waste at TPS, lack of community habits in sorting types of waste, limited trucks and trucks that are damaged so they stop working. operating waste transportation for 4 months, this has caused the volume of waste to increase at the TPS. The conclusion of this research is that waste management at the Perumnas Mandala TPS is not optimal, it is recommended that the government and the private sector improve facilities and infrastructure as well as collaborate with the community in managing waste well.